Crusades the struggle for the Holy Lands - Rice, Melanie; Rice, Christopher; Gravett, Christopher 1951-; Dennis, Peter 1950- (New York : Dorling Kindersley Pub., 2001)
A history of the Crusades, the series of wars fought by knights to defend Christianity in the Holy Land.
Keywords: Crusades -- Juvenile literature; Crusades